Islamic Religious Education in the Perspective of Prophetic Education in Junior High School: Pembelajaran Pendidikan Agama Islam Dalam Perspektif Pendidikan Profetik Di SMP - Afifuddin Afifuddin; Duski Samad; Muhammad Zalnur (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
This study aims to describe the implementation of Islamic Religious Education (PAI) learning from the perspective of prophetic education at SMP Negeri 26 Padang. The research focuses on three aspects: (1) the learning process of PAI covering the subjects of faith, worship, morals, and social relations (muamalah); (2) the methods used by PAI teachers to internalize prophetic values (transcendence, humanization, and liberation); and (3) the evaluation of PAI learning outcomes in shaping students’ morals and characterThis research employed a qualitative approach with a field study method. Data were collected through observation, in-depth interviews with teachers and students, and documentation of PAI learning activities. The data were analyzed through data reduction, data presentation, and conclusion drawing, with validation conducted through source and method triangulation The findings reveal that: (1) the PAI learning process at SMP Negeri 26 Padang has integrated prophetic values, although it is still dominated by the cognitive aspect; (2) the learning methods applied by teachers include lectures, discussions, habituation, and role-modeling, most of which are aligned with prophetic principles but still require more interactive innovation; and (3) PAI learning evaluation not only emphasizes cognitive achievement but also considers affective and moral aspects, thereby directing assessment toward the prophetic education model This study concludes that the implementation of prophetic education in PAI learning at SMP Negeri 26 Padang contributes to the formation of students’ character, although it requires strengthened learning strategies to be more effective and comprehensive